Drivers of Pine Island Glacier speed-up between 1996 and 2016 - de Rydt, Jan; Reese, Ronja; Paolo, Fernando S.; Gudmundsson, Hilmar (The Cryosphere, 2021)
Pine Island Glacier in West Antarctica is among the fastest changing glaciers worldwide. Over the last 2 decades, the glacier has lost in excess of a trillion tons of ice, or the equivalent of 3 mm of sea level rise. The ongoing changes are thought to have been triggered by ocean-induced thinning of its floating ice shelf, grounding line retreat, and the associated reduction in buttressing forces. However, other drivers of change, such as large-scale calving and changes in ice rheology and basal slipperiness, could play a vital, yet unquantified, role in controlling the ongoing and future evolution of the glacier. In addition, recent studies have shown that mechanical properties of the bed are key to explaining the observed speed-up. Here we used a combination of the latest remote sensing datasets between 1996 and 2016, data assimilation tools, and numerical perturbation experiments to quantify the relative importance of all processes in driving the recent changes in Pine Island Glacier dynamics. We show that (1) calving and ice shelf thinning have caused a comparable reduction in ice shelf buttressing over the past 2 decades; that (2) simulated changes in ice flow over a viscously deforming bed are only compatible with observations if large and widespread changes in ice viscosity and/or basal slipperiness are taken into account; and that (3) a spatially varying, predominantly plastic bed rheology can closely reproduce observed changes in flow without marked variations in ice-internal and basal properties. Our results demonstrate that, in addition to its evolving ice thickness, calving processes and a heterogeneous bed rheology play a key role in the contemporary evolution of Pine Island Glacier.